Realization of joint childrens and youth recreational programs aimed at overcoming adaptive barriers of children - migrants - Медведь, Элеонора (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
The article deals with the issue of migration in contemporary Russia which is actively explored in political, scientific (economic, sociological, etc.) and pedagogical discussions. Drawing attention to the problem of socio-cultural adaptation and integration of migrant children into urban social environment has a significant role in the process of professional training of students.